The Prospects of Legal Norms Harmonization in the Field of Proprietary Rights in BRICS Countries (on the Example of Brazil and China) - Natalia V Badaeva (RUDN Journal of Law, 2017)
The article concerns the problem of prospects and ways of the legal norms harmonization in the field of proprietary rights in BRICS countries (on the example of Braziland China). The new Civil Code of Brazil adopted in 2002 was examined as the main act dealing with the rights in rem. It reflected all important changes which fixing was required in the Brazilian society during the modern period. In the field of the proprietary rights the emphasis was placed on establishment of the principle of social function of property, reducing terms of an acquisitive prescription and partial review of system of the proprietary rights in the codified act. The Chinese civil legislation is not codified yet, so Proprietary Rights Act of 2007 contents all basic provisions on the subject. This act fully fixes the social and economic features established in the Chinese society, considers traditions and customs, and also provides participants of a business community with a comprehensive protection of the proprietary rights. The law has features of the complex act as it contains a set of regulations of administrative and legal nature along with rules of the civil nature. In conclusion some proposals were formulated to reach the goal of the harmonization of BRICS countries legislation concerning rights in rem. The member-states of BRICS should understand the necessity to move to the harmonization and to continue adopting legal institutions of other legal systems with appropriate interpretation. The denial of conservatism in the determined rules may help to reach success and to harmonize the legislation of BRICS countries. The unification of civil legal regulation will give a good direction to increase the cooperation between member-states of BRICS.